Hack the anthropologist: Translating source code, adapting research ethics. - Gitzen, Timothy (Human Organization, 2026)
How might we apply anthropological research ethics to research conducted in tech organizations, especially those that are open source and open access? In this article I reflect on my two-year volunteer work with a civic tech nonprofit organization based in Los Angeles, during which I translated and adapted anthropological ethics into research ethics guides geared towards UI/UX researchers. Writing these guides involved both contemplation and translation of anthropological methods and ethics, and a consideration of how to adapt research ethics to the organization's primary interfaces—GitHub and Google Workspace. I introduce the concept of open-source anthropology as a kind of anthropology concerned with translating and adapting our source code—our methods, training, and ethics—to non-academic audiences, and not just making our research open access. Open-source anthropology is an adaptation of anthropological research ethics elsewhere and otherwise, and it is the co-creation of research methods and ethics, making our source code truly open source. PLAIN LANGUAGE SUMMARY: In this article, I describe my experiences crafting qualitative research ethics guides for a civic tech nonprofit. The goal of the research ethics guides is to provide researchers in tech industries open source and open access guidelines for ethically conducting qualitative research (e.g., interviews) with human participants. Upon reflection, I concluded not only the usefulness of adapting anthropological research ethics outside of anthropology and in civic tech settings, but the importance of making anthropological research ethics and methods open source. This means that anthropologists should collectively craft and amend ethics and methods when conducting anthropological research like the ways I adapted anthropological research ethics to a civic tech nonprofit. SOCIAL MEDIA STATEMENT: By working with a civic tech nonprofit, Timothy Gitzen calls for an open-source anthropology that adapts anthropological research ethics and methods outside of anthropology.